Investigation of the OS-9/Grp94 interaction and its role in Endoplasmic Reticulum-Associated Degradation (ERAD) - Jones, S (2014)
Proteins that misfold or are improperly assembled in the endoplasmic reticulum (ER) are exported to the cytosol to be degraded via the ubiquitin-proteasome pathway in a process termed ER-associated degradation (ERAD). The ER resident lectin OS-9 occupies a central role, linking recognition to the delivery of aberrant proteins to the membrane-embedded SEL1L/Hrd1 ubiquitin-ligase complex. Additionally, OS-9 interacts with Grp94, the ER-resident Hsp90 family member, in a manner that is mutually exclusive of its interaction with SEL1L. To further characterise the complexes formed by OS-9 with SEL1L and Grp94, an extensive series of OS-9 truncations/deletions were generated and the resulting co-precipitation profiles compared. It was found that OS-9 interacts with Grp94 in the ER lumen and involves the C-terminal domain of OS-9. More precisely, a 65 a. a. region (OS-9443-507) is necessary for OS-9/Grp94 binding, which was designated the 94BR (Grp94 binding region). Naturally occurring point mutations and alternative splice variants within this region were compromised for binding to Grp94 but not SEL1L or substrate, indicating a highly specific interaction. A melanoma cell line derived from a lymph node metastasis and homozygous for a somatic OS-9 mutation (P446L) exhibited an increased rate of growth when compared to a parental counterpart with one wild type allele, suggesting that disruption of the OS-9:Grp94 interaction may confer an activity that favours tumour progression. These studies point toward functional consequences when OS-9 partitioning between Grp94 and SEL1L is altered.